The purchase intention of online home-based food products among Kelantanese / Siti Anis Adilah Tarmazi ... [et al.] - Tarmazi, Siti Anis Adilah; Mohd Ali, Najua; Ismail, Suriaty; Ab. Aziz, Wan Siti Nor Azma (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
In Malaysia, online home-based food products business had shown the increase during Movement Control Order (MCO). Buying food online has a significant effect on local consumers when as an example, 99 individuals have been confirmed to seek medical attention for symptoms of food poisoning and some have been hospitalised for foam pudding bought online (Bernama, 2020). Thus, the purpose of this study is to investigate the consumers' level of knowledge, attitude and perception towards food safety affecting consumers' intention to purchase online home-based food product. A quantitative study has been through with 138 respondents from Kelantan was decided using power analysis. A correlation analysis was conducted to determine the strength of the linear correlation between variables. The finding revealed that consumers' knowledge had the moderate positive relationship with purchase intention, followed by strong positive correlation between consumers' attitude and purchase intention. Meanwhile, consumers' perception had the moderate positive relationship with purchase intention. From the findings it are often concluded that buyers in Kelantan are very concern towards hygiene and in normal face to face setting this is often one among the factors which will be observed by consumers before making purchases. Additionally, there's a requirement for the regulations and legislation towards home-based online food provider and local agencies where they ought to monitor this business to make sure that there's no food safety issues arise in the future especially in Kelantan.